2008
DOI: 10.1021/bi8009778
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation Analysis of IgLON Family Proteins in Rat Brain by Liquid Chromatography and Multiple-Stage Mass Spectrometry

Abstract: IgLON family proteins, including limbic-associated membrane protein (LAMP), opioid-binding cell adhesion molecule (OBCAM), neurotrimin, and Kilon, are immunoglobulin (Ig) superfamily cell adhesion molecules. These molecules are composed of three Ig domains and a glycosylphosphatidylinositol (GPI) anchor and contain six or seven potential N-glycosylation sites. Although their glycosylations are supposed to be associated with the development of the central nervous system like other Ig superfamily proteins, they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The N-glycan structure of neurotrimin and LAMP in the adult rat brain has previously been reported (Itoh et al, 2008), in which the structure of the identified Nglycans was consistent with sialylated A2G´2F on neurotrimin, but not on LAMP.…”
Section: Discussionsupporting
confidence: 54%
“…The N-glycan structure of neurotrimin and LAMP in the adult rat brain has previously been reported (Itoh et al, 2008), in which the structure of the identified Nglycans was consistent with sialylated A2G´2F on neurotrimin, but not on LAMP.…”
Section: Discussionsupporting
confidence: 54%
“…IgLONs are members of the immunoglobulin (Ig) superfamily of cell adhesion molecules and are the most abundant glycosylphosphatidylinositolanchored proteins expressed in neurons (16). The IgLON proteins contain three immunoglobulin domains followed by a glycosylphosphatidylinositol anchor protein and possess 6 -7 potential glycosylation sites (17). IgLON family members include neurotrimin (NTM), opioid-binding cell adhesion molecule (OBCAM), limbic system-associated membrane protein (LSAMP), and neuronal growth regulator 1 (NEGR1) (16,18,19).…”
mentioning
confidence: 99%
“…In addition to its GPI anchor, most characterized GPI-APs also possess additional carbohydrate modifications such as N-and/or O-linked glycans (Fig. 1A) [1][2][3][4].…”
mentioning
confidence: 99%